Composite processing preparation method for synergistically enhancing strength-plasticity of heterostructure Mg-Sn alloy
Through the composite processing methods of cast alloy preparation, solution heat treatment, low-temperature extrusion processing and room temperature rolling processing, a multi-scale heterostructure Mg-Sn alloy is constructed, which solves the problem of insufficient room temperature strength and plasticity of magnesium alloys, achieves synergistic improvement of strong-plasticity, and simplifies the process flow and reduces production costs.
Patent Information
- Application Number
- CN202510079623.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to effectively improve the room temperature strength and plasticity of magnesium alloys in industrial applications, and the processing technology is complex and costly, making it difficult to produce in large quantities.
Multi-scale heterostructure alloys are constructed using composite processing methods of cast alloy preparation, solution heat treatment, low-temperature extrusion processing and room temperature rolling processing, including high volume fraction small-angle grain boundaries, twins, nano-scale particle phases and bimodal grain structures composed of fine and coarse crystals.
The strong-plastic synergistic performance of magnesium alloys is significantly improved through composite processing methods, the ultimate tensile strength and plasticity are improved by 3% and 82%, respectively, and the process flow is simplified, the production cost is reduced, and it is suitable for large-scale production.
Smart Images

Figure CN119736502A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal material processing, and in particular to a composite processing preparation method for synergistically enhancing the strength and plasticity of a heterogeneous structure Mg-Sn alloy. Background Art
[0002] In recent years, magnesium (Mg) alloys have attracted increasing attention for their potential in lightweight applications in new energy vehicles, aerospace and electronics industries due to their low density, high specific strength and excellent damping properties. Compared with aluminum alloys and steel, the low strength and low ductility of magnesium alloys at room temperature have greatly restricted their development, especially in a series of forged components. In fact, it is indeed crucial to improve ductility while maintaining good strength. It is well known that the limited room temperature ductility of magnesium alloys mainly stems from their unique hexagonal close-packed (HCP) crystal structure. This structure exhibits relatively low symmetry and limited slip systems at room temperature, mainly basal slip. A single basal slip cannot adapt well to uniform plastic deformation. Therefore, it is necessary for deformed magnesium alloys to activate non-basal slip. In addition, due to the orientation distribution of grains, the existence of basal texture in deformed alloys also poses challenges to the activation of non-basal slip. At present, alloying and heat treatment are often used to improve the strength and plasticity of deformed magnesium alloys. However, alloying and heat treatment inevitably increase the cost of the alloy, which is not conducive to its engineering application.
[0003] The design and construction of heterogeneous structures are the key to improving the high strength and plasticity of magnesium alloys at room temperature. In recent years, by constructing and introducing microstructural heterogeneity within the material organization, including gradient structure, non-uniform lamellar structure, mixed crystal structure and dual-phase structure, the synergistic improvement of strength and plasticity of materials at room temperature can be achieved, which provides a new idea for breaking the contradiction between strength and plasticity of traditional uniform organizational materials. Hot working is an effective means to design and construct heterogeneous structures. Hot working can improve the comprehensive mechanical properties of materials by regulating the type of heterogeneous structure (type and proportion of soft and hard zones). In recent years, many hot working technologies related to the processing of heterogeneous magnesium alloys have emerged, and such technologies play a key role in the development of high-strength and toughness magnesium alloys. Although there have been some reports on the influence of single processing on the forming or mechanical properties of heterogeneous magnesium alloys, there are still no reports on the preparation of high-strength and plastic magnesium alloys by composite processing.
[0004] The patent with publication number CN117821867A discloses a method for preparing a heterogeneous structure magnesium alloy. The specific preparation method is as follows: (1) cutting a magnesium alloy rolled plate into a bulge shape with a bulge in the middle; (2) annealing the cut sample, and then preheating the annealed sample to prepare for rolling; (3) high-temperature rolling the preheated sample, with a single pass press of 30% to 50%; (4) performing secondary annealing on the rolled sample. This method can be used to prepare a heterogeneous magnesium alloy with a fine grain size of 1 to 5 μm and a coarse grain size of 60 to 70 μm. However, this technology has the following shortcomings: (1) This method requires cutting the material into a bulge shape. The length and width of the sample are both 25 mm, the center thickness is 6 to 7 mm, and the edge thickness is 2 to 3 mm. The size specifications of the rolled sample are greatly limited, making it difficult to mass-produce and prepare. (2) The process steps used in this method are cumbersome, requiring multiple heating and heat preservation, and the processing efficiency is low, making it difficult to promote in industrial applications. (3) This method is rolled at high temperature (350-400°C), which makes it difficult to effectively inhibit grain growth during the rolling process, resulting in larger fine grains and coarse grains, which will greatly weaken the effect of alloy fine grain strengthening.
[0005] The patent with publication number CN111793778A discloses a method for preparing a high-strength and plastic mixed crystal structure magnesium alloy. The specific preparation process includes: (1) homogenizing the Mg alloy extruded sheet to eliminate the macroscopic segregation of elements in the structure and increase the solid solubility of the alloy elements; (2) subjecting the Mg alloy sheet obtained in step (1) to equal-diameter angular extrusion; (3) subjecting the equal-diameter angular extruded Mg alloy obtained in step (2) to multiple cold rolling to introduce high-density dislocations. However, the technology has the following shortcomings: the method is cumbersome and requires 2 to 3 ECAP processes for the homogenized extruded sheet, as well as 2 to 4 cold rollings and multiple heat preservation treatments. From a technical point of view, the method requires repeated temperature adjustment, changing the ECAP processing path and controlling the rolling pressure, which greatly reduces production efficiency and makes it difficult to achieve continuous production, and thus difficult to promote in process production applications.
[0006] The patent with publication number CN116463520A discloses a method for preparing a heterogeneous magnesium alloy sheet, comprising the following steps: (1) designing a mold for preparing a heterogeneous magnesium alloy sheet; (2) smelting different alloys to obtain different magnesium liquids; (3) heating the mold to 200-400°C, adding different magnesium liquids into the heated mold in layers, then quickly withdrawing the baffle and cooling to obtain a composite ingot; (4) subjecting the composite ingot to a solution treatment or a homogenization treatment; (5) heating and keeping the treated composite ingot warm, and then extruding it to obtain a composite sheet; (6) subjecting the annealed heterogeneous sheet to an aging treatment to further regulate the strength and plasticity of the heterogeneous sheet. However, this technology has the following shortcomings: (1) It is necessary to design a mold that matches the process, which increases production costs; (2) Since the extrusion temperature of the composite ingot is relatively high (250-500°C), the grain growth of the composite alloy cannot be effectively suppressed during the extrusion process, resulting in an increase in the grain size of the alloy; (3) The preparation process is long, and the heating temperature is adjusted multiple times during the preparation process. The process is lengthy and complicated, and the processing efficiency is low, which inevitably leads to high costs and difficulty in mass production, limiting the prospects for industrial applications.
[0007] The patent with publication number CN118326185A discloses a method for preparing an Al2Y compound particle reinforced plasticized heterogeneous magnesium alloy. The specific preparation process includes: step one, batching; step two, alloy smelting; step three, pouring; step four, heat treatment; step five, machining; step six, extrusion deformation processing. Although the process flow is simple, the introduction of Al2Y compound particle phase into the alloy by adding Mg-13Al2Y intermediate alloy increases the production cost. In addition, due to the high extrusion deformation processing temperature (280~350℃), it is difficult to effectively inhibit the grain growth during the extrusion process, resulting in larger fine grain and coarse grain sizes, which will greatly weaken the effect of alloy fine grain strengthening, thereby affecting the mechanical properties of the alloy.
[0008] It can be seen that although there are some partial reports on the influence of single processing on the forming or mechanical properties of heterogeneous structure magnesium alloys at this stage, there is still no report on the preparation of high-strength and plastic magnesium alloys by composite processing. And due to the high processing temperature, complex process and the need to prepare special molds, the microstructure of heterogeneous structure magnesium alloys prepared by single processing is coarsened, and its mechanical properties need to be further improved. Therefore, an advanced processing and preparation technology with low cost, simple process and conducive to synergistically improving the strength and plasticity of grain heterogeneous structure magnesium alloys should be further developed. Use low cost, existing equipment and simple process to achieve the construction of grain heterogeneous structure magnesium alloys with fine and coarse grains in binary Mg-Sn alloys, and then synergistically improve the strength and plasticity of the alloy through composite processing technology. In order to promote the application of Mg-Sn alloys in industrial production. Summary of the invention
[0009] In view of the above problems, the present invention provides a composite processing preparation method for synergistically enhancing the strength-plasticity of heterostructured Mg-Sn alloys, which solves the problems in the prior art of low room temperature strength and poor plasticity of binary Mg-Sn alloys and difficulty in further synergistically improving the strength-plasticity of heterostructured alloys.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The object of the present invention is to provide a composite processing preparation method for synergistically enhancing the strength and plasticity of a heterogeneous structure Mg-Sn alloy, wherein the target alloy is Mg-7Sn (wt.%), and the process comprises: preparation of a cast alloy, solution heat treatment, low temperature extrusion processing and room temperature rolling processing, specifically comprising the following steps: S1: Preparation of cast alloy: magnesium ingot and tin particles are used as raw materials. The raw materials are weighed according to the mass percentage according to the target alloy composition, and preheated and dried at 200°C; the dried magnesium ingot is placed in a crucible and a covering agent is added. The crucible is placed in a melting furnace protected by argon gas, and the temperature is raised to 720°C at a rate of 5°C / min and kept warm for 30 minutes. After the magnesium block is completely melted, the tin particles are placed in a colander, inserted into the metal liquid surface and stirred for 2 minutes, the furnace cover is covered and argon gas is continued to be introduced. After the temperature of the melting furnace rises to 740°C, the temperature is kept warm for 30 minutes. min to ensure that the solution can be evenly diffused; after heat preservation, the refining agent is added to the metal solution and stirred immediately until the surface of the solution shows metallic luster, and then the slag on the surface of the metal solution is removed with a smelting spoon, and the smelting furnace cover is covered to keep the temperature; finally, the melt is introduced into a semi-continuous casting crystallizer whose outer wall is cooled by water, and a solidified shell is formed after solidification and crystallization. The traction mechanism of the ingot casting machine drives the base and the solidified shell that has solidified on the base to move downward continuously and evenly at a certain speed, and finally a cast alloy is prepared; S2: Solution treatment: Since magnesium alloy is easily oxidized at high temperature, the alloy needs to be protected. Therefore, under the protection of argon, the oxide layer on the surface of the cast alloy is removed and placed in a resistance furnace. The temperature is raised to 480°C at 10°C / min and kept for 12 hours. Then it is taken out and water quenched to obtain a solid solution alloy. S3: Extrusion processing: Before extrusion, the two ends of the solid solution alloy are cut to retain the middle part, and the oxide layer is removed on a milling machine to use as the extrusion blank, and the blank is kept warm at 230°C; the extrusion die is then preheated in a drying oven; during extrusion, MoS2 is used as a lubricant, the extrusion die is installed at the discharge port, and then the preheated extrusion blank is placed in the extrusion barrel (the extrusion barrel is the pipe in the extruder, and the blank is placed in the pipe and extruded through the extrusion die) for extrusion. In order to prevent the preheating in the extrusion plate after extrusion, which causes the grain size to grow and affects the mechanical properties of the extruded alloy, air cooling or water cooling is used for rapid cooling after extrusion; the unevenly deformed parts at both ends of the extruded sample are cut off, and the extruded alloy in the middle part is retained; S4: rolling process: when rolling is carried out at room temperature, the extruded alloy of step S3 is used as the rolling stock; before rolling, the stock is accurately placed on the workbench of the rolling equipment so that it is in a lateral position along the extrusion direction to ensure the directionality and uniformity of the rolling process, and multiple rolling passes with a small downward pressure are performed; during rolling, MoS2 is used as a lubricant; during the rolling process, for each rolling operation, the downward pressure is strictly controlled to 1%, and the pressure is applied slowly and steadily through a precise pressure regulating device to gradually deform the stock; multiple rolling passes are continued until the total downward pressure reaches 12%, and the target alloy is obtained.
[0011] Furthermore, in step S1, the purity of the magnesium ingot is 99.95%, and the purity of the tin particles is 99.99%.
[0012] Furthermore, in step S1, the covering agent is a mixture of NaCl and KCl in a mass ratio of 3:1.
[0013] Furthermore, in step S1, the refining agent is hexachloroethane (C2Cl6).
[0014] Furthermore, in step S2, after the solution treatment is completed, the alloy needs to be rapidly cooled in water.
[0015] Furthermore, in the step S3, in order to prevent the friction between the billet and the die from generating heat during the extrusion process, causing the extrusion temperature to be higher than the set temperature, the preheating temperature of the extrusion die is more than 20°C lower than the extrusion temperature; in order to prevent the alloy from undergoing complete dynamic recrystallization and thus obtaining a homogeneous material, it is necessary to perform extrusion at a low temperature, the extrusion temperature is 230°C, the extrusion speed is 3.5 mm / s, and the extrusion ratio is 9:1.
[0016] Furthermore, in step S3, the extrusion process is forward extrusion.
[0017] Furthermore, in step S4, the rolling speed is always maintained at 50 rad / min.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention can construct a multi-scale heterogeneous structure alloy in a magnesium alloy, which contains a high volume fraction of small-angle grain boundaries, partial twins, nanoscale particle phases and a bimodal grain structure composed of fine grains (2-3 μm) and coarse grains (10-20 μm).
[0019] (2) The low-temperature extrusion process plus room-temperature rolling composite processing process proposed in the present invention can effectively increase the contact area of the heterogeneous interface (the contact area between coarse grains and fine grains), thereby improving the heterogeneous deformation induced stress (HDI) and HDI work hardening ability of the alloy; at the same time, it is beneficial to weaken the basal texture strength, thereby stimulating the multiple slip mechanisms of the alloy, and ultimately improving the strength-plasticity of the alloy synergistically.
[0020] (3) The present invention can achieve the preparation of a magnesium alloy with a synergistically improved strength and plasticity of a grain heterogeneous structure only by combining a direct extrusion process with a room temperature rolling process, and can prepare large-size plates; at the same time, there is no need to add other high-cost intermediate alloys, nor is there a need to design specific molds; the deformation process is simple, which can improve the alloy yield, save the alloy preparation cost, and facilitate commercial promotion and application.
[0021] (4) The present invention can control the contact area between coarse grains and fine grains in the heterogeneous grain structure by controlling the extrusion process and the extrusion plus rolling composite processing process, so that the strength and plasticity of the alloy are synergistically improved.
[0022] (5) The present invention provides an effective method for the microstructure regulation and mechanical property improvement of grain heterogeneous magnesium alloys. The strength of the grain heterogeneous alloys prepared by the composite processing technology exceeds that of the currently reported binary Mg-Sn alloys and is comparable to some ternary and even quaternary Mg-Sn alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic flow chart of the composite processing preparation method for synergistically enhancing the strength and plasticity of heterostructured Mg-Sn alloy of the present invention; Figure 2 shows the scanning electron microstructure, grain size distribution, IPF and PF diagrams of the 230°C extruded alloy of the present invention (a)-(d); the scanning electron microstructure, grain size distribution, IPF and PF diagrams of the EBSD of the extruded + rolled composite processed alloy; (i) is the room temperature tensile engineering stress-strain curve of the extruded alloy and the extruded + rolled composite processed alloy; (j) is a comparison diagram of the mechanical properties of the extruded alloy and the extruded + rolled composite processed alloy. DETAILED DESCRIPTION
[0024] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.
[0026] In this embodiment, the components of the semi-continuous casting equipment are: a crystallizer (using a shell and a sleeve made of graphite); a traction mechanism (using a wire rope, a chain or hydraulic means to achieve traction); a furnace system (resistance furnace); a cooling system (including cooling of the crystallizer and other components, and removing heat through circulating cooling water); a control system (using a programmable logic controller (PLC) or the like to accurately control parameters such as temperature and speed during the casting process).
[0027] Example 1 This embodiment provides a composite processing preparation method for synergistically enhancing the strength and plasticity of a heterogeneous structure Mg-Sn alloy, wherein the target alloy is Mg-7Sn (wt.%), and the process includes: preparation of a cast alloy (semi-continuous casting of magnesium alloy), solution treatment, low-temperature extrusion processing (extrusion deformation) and room temperature rolling processing (rolling deformation), as shown in the flow chart. Figure 1 As shown, the following steps are included: S1: Preparation of cast alloy: Use magnesium ingots with a commercial purity of 99.95% and tin particles with a purity of 99.99% as raw materials, weigh the raw materials according to the mass percentage according to the target alloy composition, preheat and dry at 200°C; put the dried magnesium ingot into a crucible and add a covering agent (a mixture of NaCl and KCl with a mass ratio of 3:1), put the crucible into a melting furnace protected by argon, heat it to 720°C at 5°C / min and keep it warm for 30 minutes, after the magnesium block is completely melted, put the tin particles into a colander, put it under the metal liquid surface and stir for 2 minutes, cover the furnace cover and continue to introduce argon, and keep it warm for 30 minutes after the furnace temperature of the melting furnace rises to 740°C to ensure that the solution can be evenly diffused; after keeping warm, add the refining agent (C2Cl6) to the metal solution and stir it immediately until Stop when the metal luster appears on the surface of the melt, use a smelting spoon to remove the slag on the surface of the melt, and cover the smelting furnace to keep it warm; finally, evenly introduce the melt into a semi-continuous casting crystallizer with water-cooled outer walls, and rapidly solidify and crystallize under the joint action of the crystallizer wall and the crystallizer base, and form a relatively strong solidified shell; when the horizontal liquid level of the melt in the crystallizer reaches a certain height, the traction mechanism of the ingot casting machine drives the base and the solidified shell solidified on the base to move downward continuously and evenly at a certain speed; the part that has solidified into the ingot and separated from the crystallizer is immediately directly cooled by the secondary cooling water from the lower edge of the crystallizer, and the crystal layer of the ingot is continuously pushed toward the central area and completely solidified and crystallized, and finally an alloy ingot (cast alloy) of φ=90mm is prepared; S2: Solution treatment: Since magnesium alloy is easily oxidized at high temperature, the alloy needs to be protected. Therefore, under the protection of argon, the cast alloy with the oxide layer removed is placed in a resistance furnace, heated to 480°C at 10°C / min and kept for 12 hours, then taken out and water quenched to obtain a solid solution alloy; S3: Extrusion processing: Before extrusion, the two ends of the solid solution alloy are cut to retain the middle part, and the oxide layer is removed on a milling machine to serve as the extrusion blank, and the blank is kept warm at 230°C; the extrusion die is then preheated in a drying oven. To prevent the friction between the blank and the die from generating heat during the extrusion process, which causes the extrusion temperature to be higher than the set temperature, the preheating temperature of the extrusion die is at least 20°C lower than the extrusion temperature; during extrusion, MoS2 is used as a lubricant, and the preheated sample is placed in the extrusion barrel (the extrusion barrel is the pipe in the extruder, and the blank is placed in the pipe and extruded through the extrusion die) for forward extrusion. To prevent the alloy from undergoing complete dynamic recrystallization and thus obtaining a homogeneous material, it is necessary to extrude at a low temperature, with an extrusion temperature of 230°C, an extrusion speed of 3.5mm / s, and an extrusion ratio of 9:1; to prevent the preheating in the extrusion plate after extrusion from causing the grain size to grow and affecting the mechanical properties of the extruded alloy, air cooling or water cooling is used for rapid cooling after extrusion; the unevenly deformed parts at both ends of the extruded sample are cut off, and the extruded alloy in the middle part is retained; S4: rolling process: when rolling is performed at room temperature, the extruded alloy of step S3 is used as the rolling stock; before rolling, the stock is accurately placed on the workbench of the rolling equipment so that it is in a lateral position along the extrusion direction to ensure the directionality and uniformity of the rolling process, and multiple rolling with a small downward pressure is performed; during the rolling process, the rolling speed is always maintained at 50rad / min, and for each rolling operation, the downward pressure is strictly controlled to be 1%, and the pressure is applied slowly and steadily through the precise pressure regulating device to gradually deform the stock; after each rolling, the thickness, flatness and surface quality of the stock are carefully inspected and measured, and the relevant data are recorded for subsequent analysis and process adjustment. Continue multiple rolling passes until the total downward pressure reaches 12%, and the target alloy is obtained.
[0028] The microstructure and mechanical properties of the extruded alloy and the extrusion + rolling composite processed alloy (grain heterogeneous structure alloy) in the above Example 1 were tested, and the results are shown in FIG2 .
[0029] In Figure 2, (a)-(d) are the scanning electron microstructure, grain size distribution, EBSD IPF and PF maps of the 230℃ extruded alloy; (e)-(h) are the scanning electron microstructure, grain size distribution, EBSD IPF and PF maps of the extrusion + rolling composite processing alloy. By comparison, it can be found that both single extrusion and extrusion plus rolling composite processing form a grain heterogeneous structure composed of fine recrystallized grains and coarse hot-worked grains. The grain size of fine grains is between 2-3μm, and the grain size of coarse grains is between 10-20μm. The extruded alloy prepared by low-temperature extrusion has a strong basal surface texture, which makes it difficult to start basal surface slip, resulting in poor plasticity of the alloy. For the extrusion + rolling composite alloy prepared by rolling composite processing, on the one hand, the coarse grains are further elongated along the rolling direction, resulting in an increase in the contact area of the heterogeneous interface (the contact surface between coarse grains and fine grains), which increases the heterogeneous deformation induced stress (HDI), thereby producing stronger HDI work hardening, which synergistically improves the strength and plasticity of the alloy. On the other hand, rolling causes the formation of {10-12} tensile twins in the alloy, causing the texture type of some coarse grains to change from basal texture to non-basal texture, making the alloy easier to activate basal slip, thereby improving the plasticity of the alloy. In addition, due to the increase in residual strain inside the alloy caused by rolling, a large number of small-angle grain boundaries are formed in the coarse grains, and the high volume fraction of small-angle grain boundaries is conducive to the synergistic improvement of the strength and plasticity of the alloy.
[0030] By comparing the room temperature tensile engineering stress-strain curves of the two alloys in Figure (i), it can be found that the composite processed alloy has good strength-plastic matching, with an ultimate tensile strength of 315.7MPa and a plasticity of 16.82%, which are 3% and 82% higher than those of the extruded alloy, respectively. By comparing the mechanical properties of the alloys in Figure (j), it can be found that the strength and plasticity of the alloy prepared by composite processing are higher than those of other deformed binary Mg-Sn alloys reported so far, and are comparable to some deformed ternary and even quaternary Mg-Sn alloys.
[0031] Through the observation of the microstructure and mechanical properties of the grain heterostructure alloy prepared by the above-mentioned single extrusion deformation process and the extrusion plus rolling composite process, it can be found that the present embodiment can weaken the basal texture strength of the traditional single-processed Mg-Sn alloy through composite processing, and increase the contact area of the heterogeneous interface, thereby optimizing the mechanical properties of the alloy. And the binary Mg-Sn alloy prepared in this embodiment has good strength-plastic matching, which is higher than other deformed binary Mg-Sn alloys reported so far and can be comparable to ternary or even quaternary deformed alloys. Therefore, the composite processing preparation method for synergistically enhancing the strength-plasticity of the grain heterostructure Mg-Sn alloy proposed in this embodiment is feasible.
[0032] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite processing preparation method for synergistically enhancing the strength and plasticity of heterostructured Mg-Sn alloy, characterized in that: The specific steps include: S1: Preparation of cast alloy: magnesium ingot and tin particles are used as raw materials, preheated and dried at 200°C; the dried magnesium ingot is placed in a crucible and a covering agent is added, the crucible is placed in a melting furnace protected by argon gas, the temperature is raised to 720°C at 5°C / min and kept warm for 30 minutes, after the magnesium block is completely melted, the tin particles are placed in a colander, inserted below the metal liquid surface and stirred for 2 minutes, the furnace cover is covered and argon gas is continued to be introduced, and the temperature of the melting furnace is kept warm for 30 minutes after the furnace temperature rises to 740°C; after keeping warm, the refining agent is added to the metal solution, and stirring is immediately carried out until a metallic luster appears on the surface of the solution, and then the stirring is stopped, and the slag on the surface of the metal solution is removed with a melting spoon, and the melting furnace cover is covered to keep warm; finally, the melt is introduced into a semi-continuous casting crystallizer whose outer wall is cooled by water, and a solidified shell is formed after solidification and crystallization. The traction mechanism of the ingot casting machine drives the base and the solidified shell that has solidified on the base to move downward continuously and evenly at a certain speed, and finally a cast alloy is prepared; S2: Solution treatment: Under argon protection, the oxide layer on the surface of the cast alloy is removed and the alloy is placed in a resistance furnace, heated to 480°C at 10°C / min for 12 hours, and then taken out for water quenching to obtain a solid solution alloy; S3: Extrusion processing: Before extrusion, the two ends of the solid solution alloy are cut to keep the middle part, and the oxide layer is removed on a milling machine to use as the extrusion blank, and the blank is kept warm at 230°C; the extrusion die is then preheated in a drying oven; during extrusion, MoS2 is used as a lubricant, the extrusion die is installed at the discharge port, and then the preheated extrusion blank is placed in the extrusion barrel for extrusion, and air cooling or water cooling is used for rapid cooling after extrusion; The unevenly deformed parts at both ends of the extruded sample were cut off, and the extruded alloy in the middle was retained; S4: rolling process: when rolling is carried out at room temperature, the extruded alloy of step S3 is used as the rolling stock; before rolling, the stock is accurately placed on the workbench of the rolling equipment so that it is in a lateral position along the extrusion direction and is rolled multiple times with a small downward pressure; during rolling, MoS2 is used as a lubricant; during the rolling process, for each rolling operation, the downward pressure is strictly controlled to 1%, and multiple rolling passes are continued until the total downward pressure reaches 12%, thereby obtaining the target alloy.
2. The composite processing preparation method for synergistically enhancing the strength and plasticity of heterostructured Mg-Sn alloy according to claim 1, characterized in that: In step S1, the purity of the magnesium ingot is 99.95%, and the purity of the tin particles is 99.99%.
3. The composite processing preparation method for synergistically enhancing the strength and plasticity of heterostructured Mg-Sn alloy according to claim 1, characterized in that: In the step S1, the covering agent is a mixture of NaCl and KCl in a mass ratio of 3:
1.
4. The composite processing preparation method for synergistically enhancing the strength and plasticity of heterostructured Mg-Sn alloy according to claim 1, characterized in that: In the step S1, the refining agent is hexachloroethane.
5. The composite processing preparation method for synergistically enhancing the strength and plasticity of heterostructured Mg-Sn alloy according to claim 1, characterized in that: In the step S3, the preheating temperature of the extrusion die is at least 20°C lower than the extrusion temperature; the extrusion temperature is 230°C, the extrusion speed is 3.5 mm / s, and the extrusion ratio is 9:
1.
6. The composite processing preparation method for synergistically enhancing the strength and plasticity of heterostructured Mg-Sn alloy according to claim 1, characterized in that: In step S3, the extrusion process is forward extrusion.
7. The composite processing preparation method for synergistically enhancing the strength and plasticity of heterostructured Mg-Sn alloy according to claim 1, characterized in that: In step S4, the rolling speed is always maintained at 50 rad / min.
Citation Information
Patent Citations
Method for preparing high-strength and high-plasticity magnesium alloy with mixcrystal structure
CN111793778A
Preparation method of magnesium alloy plate with heterostructure
CN116463520A
Preparation method of heterostructure magnesium alloy
CN117821867A
Preparation method of Al2Y compound particle reinforced plasticized magnesium alloy
CN118326185A